The importance of Java and CORBA in medicine. - Forslund, D. W. (American Medical Informatics Association, 1997)
One of the most powerful tools available for telemedicine is a multimedia medical record accessible over a wide area and simultaneously editable by multiple physicians. The ability to do this through an intuitive interface linking multiple distributed data repositories while maintaining full data integrity is a fundamental enabling technology in healthcare. We discuss the role of distributed object technology using Java and CORBA in providing this capability including an example of such a system (TeleMed) which can be accessed through the World Wide Web. Issues of security, scalability, data integrity, and usability are emphasized.